PENGARUH KUALITAS KOMITE AUDIT, KUALITAS DEWAN KOMISARIS, KEPEMILIKAN INSTITUSIONAL DAN KEPEMILIKAN MANAJEMEN TERHADAP PRAKTEK MANAJEMEN LABA DAN KINERJA KEUANGAN SERTA IMPLIKASINYA TERHADAP NILAI PERUSAHAAN (Survey Pada Perusahaan Listing di PT. Bursa - Harnovinsah Harnovinsah (Indonesian Journal of Economics and Business, 2011)
Financial report is an important factor for inventors to make investment decision in capital market. Publicly financial report which has relevant information will be reacted by market player. Many investors and other users of financial report do not pay attention to the process of publishing financial report, so it pushes the emergence of dysfunctional behaviours like earning management practices. The purpose of this research is to study and to find out empirically of research’s evidence about the influence of audit committee and board of commissioner’s quality, institution and management ownerships toward earnings management practice and financial performance and the implication toward firm value The population of this research is companies listed in Indonesian Stock Exchenge during the period 2007 – 2009 in amount of 105 companies. Based on the criteria, there are only 60 companies chosen as sample.  The Method of analysis of this research used path analysis, with the following hypotheses: (1) The Audit committee and the board of commissioner’s quality, institution and management ownership have influence on the earnings management practice. (2) The Audit committee and the board of commissioner’s quality, institution and management ownership, the earnings management practice have influence on corporate financial performance. (3) The earnings management practice and corporate financial performance have influence on  firm value The results of this study indicates (1)The audit committee quality negatively influence on earnings management practice, (2)  The board of commissioner’s quality negatively influence on earnings management practice  (3) The institutional ownership negatively influence on earnings management practice  (4) the managerial ownership negatively influence on earnings management practice but not significant, (5) simultaneously of  The audit committee  quality, The board of commissioner’s quality, institutional ownership and  managerial ownership,   and have  significant influence on earnings management practice, and (6) earnings management practice positively influence on corporate financial performance but not significant, (7) earnings management practice positively influence on  firm value, but not significant, (8) corporate financial performance positively influence on  firm value.